Time distribution characteristics of cat-eye reflected light from moving optical target - 赵延仲 孙华燕 郑勇辉 张来线 (Optoelectronics letters, 2011)
By using the Collins diffraction formula and expanding the aperture function into a fmite sum of complex Gaussian functions, an analytical formula of the time light intensity distribution for oblique Gaussian beams passing through a moving cat-eye optical lens and going back along the entrance way is deduced. By numerical computation, the variation laws of the time intensity distributions of the cat-eye reflected light with the viewing angle, imaging distance, aperture and instantaneous field of view are given. The results show that the relationship between the light intensity at the return place and the detection time is linear, and it is of inverse proportion only when the viewing angle is very large. For the staring imaging optical lens, the nonlinear extent of the time distribution curve becomes larger with the decrease of the viewing angle. For the instantaneous imaging optical lens, there is still some cat-eye reflected light when the detection system is out of the viewing field of the target lens.